Enhancing the purity and intrinsic properties of ovine dermal papilla cells through flow cytometry sorting and cellular interactions - Yuan Gou; Tingyan Hu; Lijuan Zhu; Xiaoyang Lv; Yutao Li; Rui Su; Zhenghai Song; Shanhe Wang; Wei Sun (Animal Bioscience, 2025)
Objective Dermal Papilla Cells (DPCs) play a crucial role in regulating hair follicle development and serve as a valuable in vitro model for screening and analyzing the genes associated with this process. However, current methods for isolating ovine DPCs primarily rely on mechanical techniques, which present several limitations. The aim of this study is to establish a method for isolating and culturing ovine DPCs with high purity and retaining their intrinsic properties. Methods We identified sheep DPC membrane-specific genes using single-cell transcriptomic data, validated by immunostaining and flow cytometry. Antibody-labeled DPCs were isolated, cultured, and assessed via fluorescence-activated cell sorting (FACS), comparing their purity with conventional mechanical isolation. Mechanically isolated and flow-sorted DPCs were analyzed through agglutination, cell counting kit (CCK-8), and EDU staining. Furthermore, we examined the biological properties of isolated DPCs in conditioned media using CCK-8, EDU, and quantitative reverse transcription polymerase chain reaction assays. Results PDGFRA was identified as a marker for ovine DPCs. Flow cytometry showed that PDGFRA-labeled DPCs made up 1.54% of the hair follicle cell population, with 1.92% live DPCs obtained via FACS. The isolated DPCs demonstrated agglutination and were positive for ALP, Versican, and α-SMA. Antibody labeling yielded higher DPC purity compared to mechanical isolation, highlighting its efficiency. Accordingly, the addition of conditioned media from mechanically isolated DPCs significantly enhanced agglutination, cell viability, proliferation, and inductive capacity of the sorted DPCs. However, as the number of passages increased, the sorted DPCs demonstrated significant disadvantages in cell agglutination, proliferation rate, and viability compared to mechanically isolated DPCs. Accordingly, the addition of conditioned media from mechanically isolated DPCs significantly enhanced agglutination, cell viability, proliferation, and inductive capacity of the sorted DPCs. Conclusion This study highlights the effectiveness of antibody labeling and flow cytometry for isolating functionally pure DPCs, as well as the potential of conditioned media to maintain the functional properties of these cells.